A theoretical study on superalkali-doped nanocages: unique inorganic electrides with high stability, deep-ultraviolet transparency, and a considerable nonlinear optical response. Issue 17 (5th April 2016) - Sun, Wei-Ming; Li, Xiang-Hui; Wu, Di; Li, Ying; He, Hui-Min; Li, Zhi-Ru; Chen, Jing-Hua; Li, Chun-Yan
Abstract : A series of stable inorganic electrides with a large nonlinear optical response and deep-ultraviolet transparency were theoretically designed and investigated. Abstract : By doping an Al12 N12 nanocage with superalkali Li3 O, a series of Li3 O@Al12 N12 compounds were theoretically designed and investigated for the first time. Computational results reveal that these species contain diffuse excess electrons, and thus can be regarded as inorganic electrides of a new type. As expected, these proposed electrides possess considerable first hyperpolarizabilities ( β 0 ) up to 1.86 × 10 7 au. In particular, the lowest-energy Li3 O@Al12 N12 exhibits high stability and excellent deep-ultraviolet transparency. Moreover, the effects of superalkali and nanocage subunits on the NLO responses of M3 O@Al12 N12 (M = Li, Na, K) and Li3 O@X12 Y12 (X = B, Al; Y = N, P) are systemically investigated. Results show that the respective substitution of Na3 O and B12 P12 for Li3 O and Al12 N12 can bring a larger β 0 for such electrides. This study may be significant in terms of providing an effective strategy to design thermally stable inorganic electrides as potential high-performance NLO molecules.